DARI SAKRAL KE KULTURAL: TRANSFORMASI KEAGAMAAN LOKAL DALAM ERA MODERNISASI - Jati Pamungkas (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Local religious traditions constitute an important aspect of Indonesian society and have long served as a medium for religious expression, social integration, and the preservation of cultural values. However, the processes of modernization, globalization, urbanization, and the rapid development of information technology have significantly transformed the meaning and practice of religious traditions in various regions. This article aims to analyze the transformation of local religious traditions from sacred dimensions toward cultural dimensions within the context of contemporary social change. The study employs a qualitative approach using a library research method by examining books, scholarly journal articles, and previous studies relevant to religious traditions, modernization, and social transformation. The analytical framework is based on Peter L. Berger’s Social Construction Theory, which emphasizes the processes of externalization, objectivation, and internalization in the construction of social reality. The findings reveal that modernization does not necessarily eliminate local religious traditions; rather, it encourages the reconstruction of their meanings and social functions. Many local religious practices that were previously understood primarily as sacred activities closely related to religious beliefs are now also perceived as cultural identities, instruments for preserving local heritage, mechanisms of social integration, and resources for cultural tourism. This transformation reflects an ongoing negotiation between traditional values and the demands of modernity, resulting in new forms of religious expression within society. Therefore, local religious traditions continue to survive as integral elements of social life despite experiencing shifts in meaning and orientation. The study concludes that religious traditions are socially constructed realities that are continuously reproduced and reinterpreted in response to changing social conditions. Keywords: local religious traditions, modernization, social change, social construction.